Errors in Final Report Abstracts - Wawan Hendrawan (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
This study investigates the common errors exist in the English report abstracts authored by the fourth semester students learning at a secretarial academy. The purpose of the study is to improve the outcomes of the abstracts written resides in an English report writing course. 95 abstract documents are categorized and analyzed using the frameworks from James (1998) and Richards (1974), then, interpreted descriptively using descriptive statistics. This is conducted under the umbrella of qualitative research method particularly a case study. The results demonstrate that, first, there are found several types of errors such as tense, missing word, passive and active voices, subject and verb agreement, misspelling, runs on sentence, capital letter, unnecessary word, punctuation, and incorrect use of word. Second, errors classified as grammatical categories are dominating the errors occurrences. Third, errors considered as lexical taxonomies become the least errors to happen. Fourth, the causes of errors identified are interlanguage, intralanguage, and negligence of the students when writing an English abstract. Implication for the development of abstract writing in an English report writing course is the discovered errors in the present study should be the main concern to be improved by the student writers.